Free fatty acids: potential proinflammatory mediators in rheumatic diseases. Issue 1 (27th November 2013) - Frommer, Klaus W; Schäffler, Andreas; Rehart, Stefan; Lehr, Angela; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Objectives: Due to their role in inflammatory metabolic diseases, we hypothesised that free fatty acids (FFA) are also involved in inflammatory joint diseases. To test this hypothesis, we analysed the effect of FFA on synovial fibroblasts (SF), human chondrocytes and endothelial cells. We also investigated whether the toll-like receptor 4 (TLR4), which can contribute to driving arthritis, is involved in FFA signalling. Methods: Rheumatoid arthritis SF, osteoarthritis SF, psoriatic arthritis SF, human chondrocytes and endothelial cells were stimulated in vitro with different FFA. Immunoassays were used to quantify FFA-induced protein secretion. TLR4 signalling was inhibited extracellularly and intracellularly. Fatty acid translocase (CD36), responsible for transporting long-chain FFA into the cell, was also inhibited. Results: In rheumatoid arthritis synovial fibroblasts (RASF), FFA dose-dependently enhanced the secretion of the proinflammatory cytokine IL-6, the chemokines IL-8 and MCP-1, as well as the matrix-degrading enzymes pro-MMP1 and MMP3. The intensity of the response was mainly dependent on the patient rather than on the type of disease. Both saturated and unsaturated FFA showed similar effects on RASF, while responses to the different FFA varied for human chondrocytes and endothelial cells. Extracellular and intracellular TLR4 inhibition as well as fatty acid transport inhibition blocked the palmitic acid-induced IL-6 secretion of RASF. Conclusions: The data show that FFA are not only metabolic substrates but may also directly contribute to articular inflammation and degradation in inflammatory joint diseases. Moreover, the data suggest that, in RASF, FFA exert their effects via TLR4 and require extracellular and intracellular access to the TLR4 receptor complex.